Oxygen carrier derived from ferric sludge for chemical looping combustion of MSW syngas: waste derived material performance and carbon footprint assessment - Koh Yang, Chat How Joewin (2023)
The utilization of water treatment sludge (i.e., ferric sludge) was explored as the oxygen carrier (OC) for chemical looping combustion (CLC) of municipal solid waste (MSW) syngas. The performance of ferric sludge (FS) in CLC and simultaneous HCl removal was evaluated in a bench-scale fluidized bed, and was compared with iron ore (IO) as a benchmarked OC. The results show that FS (92 %) performed better than IO (82 %) in terms of syngas combustion efficiency and FS was able to remove HCl (77 % removal efficiency) while IO was unable to remove any HCl. Comparison of reaction temperature reveals that FS performed better at lower CLC temperature between 800 °C and 850 °C. Agglomeration was observed when FS was used in extended CLC cycles. Thus, investigation of using inert α-Al2O3 support together with FS for extended CLC cycles was investigated. Agglomeration and sintering were drastically reduced and good combustion efficiency of 88 % for H2 and 74 % for CO was attained. Carbon footprint assessment illustrated that FS was superior as a greener material based on global warming potential of 20 and 100 years. Conversion of FS as an OC were characterized with 104.23 and 108.0 kgCO2/t lower than IO for GWP-20 and GWP-100, exhibiting the competitiveness in the usage of waste-derived material in CLC. Hence, FS can be considered as a novel, cost-effective, and greener OC for CLC. The co-utilization of waste-derived material and waste-derived syngas through CLC would be an integrated solution for improved circularity and sustainability.